Taking Stock of Research about Initial English Language Teacher Education in Colombia (2022)
This article presents a literature review based on research related to pre-service English language teachers (PELT) in Colombia that have been published in specialized Colombian journals during 2010-2020. The result was a corpus of 41 articles, of which I analyzed who wrote them, the research design used in each one, and the main topics covered in the research or pedagogical experiences. The results show a growing interest in research on PELTs from different epistemologies and research areas. Furthermore, researchers are increasingly conducting their research from narrative research under a critical or decolonial position. Finally, although many of the central themes revolve around teachers’ linguistic competencies and abilities in training, other issues have increased in recent years, such as teacher identity from different angles, critical pedagogies, and reflection of teaching processes.